Association between mean platelet volume and adiponectin in patients with metabolic syndrome - Marinkovic, Milos; Nesic, Jelena; Petrovic, Ivica; Jovanovic, Ivan P; Sekulic, Marija; Djukic, Svetlana; Djukic, Aleksandar (Journal of applied biomedicine, 2024)
Metabolic syndrome is a significant pro-inflammatory and pro-coagulant condition. The clinical association of adiponectin, a mainly antidiabetogenic molecule, and its interaction with platelets and platelet indices remains insufficiently investigated. The aim of our study was to investigate the association of adiponectin with platelets and platelet indices in patients with metabolic syndrome. The investigation was conducted as a cross-sectional study involving 113 subjects: 63 patients with the diagnosis of metabolic syndrome, and 50 healthy controls - with clear inclusion and exclusion criteria. The group of patients with metabolic syndrome was divided into two subgroups according to the platelet/high-density lipoprotein (HDL) ratio. The subgroup with a higher platelet/HDL ratio was prediabetic. In the same subgroup of patients, a positive correlation between the adiponectin and mean platelet volume (MPV) was seen, while linear regression (95% CI) confirmed the association. Considering that MPV is the index that indicates average platelet volume and activity, we believe this association with adiponectin can represent a protective compensatory response in patients with metabolic syndrome and prediabetes. Our results provide a basis for a more precise selection of patients in whom the future therapeutic application of recombinant adiponectin would be most effective.